Focusing on the Basic Principles of Dialysis to Optimize Antibiotic Therapy during Renal Replacement Therapy in Critically Ill Patients - Filippo Mariano; Alberto Mella; Luigi Biancone (MDPI AG, 2024)
Bacterial infections frequently occur in patients in the ICU undergoing renal dialysis using extracorporeal procedures (KRT) that can be applied for different time periods, such as Prolonged Intermittent Renal Replacement Therapy (PIRRT) or Continuous Kidney Replacement Therapy (CKRT) [...]